THE INFLUENCE OF SOCIAL MEDIA PROMOTION AND BRAND IMAGE ON THE PURCHASE DECISION OF SCARLETT WHITENING BODY LOTION PRODUCTS ON TIKTOK - Chairunnisa, Tsabita Dzikra; Scorita, Kurnia Budhy; Faisal, Bintang Akbar (Kinerja, 2025)
This study aims to analyze the influence of Social Media Promotion and Brand Image on Purchase Decisions among Scarlett Whitening Body Lotion customers on TikTok. The method used is a quantitative approach with multiple linear regression analysis and classical assumption tests. The population in the study is customers of Scarlett Whitening Body Lotion on TikTok. This research uses a questionnaire as a data collection tool with a sample size of 150 respondents, and it employs the SPSS 25 program for data processing. The test results show that the data meet the classical assumptions and the regression model is significant. Social Media Promotion (β = 0.434) and Brand Image (β = 0.513) have a positive and significant effect on Repurchase Intention (Sig. < 0.05). The R² value of 0.764 indicates that the two variables explain 76.4% of the variation in Repurchase Intention, and the remaining 31.6% is influenced by other factors outside the model. The F-test also shows a significant simultaneous effect (F = 238.378; Sig. = 0.000). Thus, it can be concluded that Social Media Promotion and Brand Image, both partially and simultaneously, have a significant effect on Purchase Decisions among Scarlett Whitening Body Lotion customers on TikTok. This model can be used as a basis for decision-making in digital marketing strategies on social media platforms.